New Choices in Undergraduate Biology Course Designs, but Use the Vision and Change ModelReview of: Building a Pathway for Student Learning: A How-to Guide to Course Design; Steven Jones, Robert Noyd, and Kenneth Sagendorf; (2014). Stylus Publishing, Sterling, VA. 139 pages. - Rachel E. A. Horak (American Society for Microbiology, 2015)
Review of: Building a Pathway for Student Learning: A How-to Guide to Course Design; Steven Jones, Robert Noyd, and Kenneth Sagendorf; (2014). Stylus Publishing, Sterling, VA. 139 pages.